Development of Scalable Culture Systems for Human Embryonic Stem Cells - Azarin, Samira M. (2010)
The use of human pluripotent stem cells, including embryonic and induced pluripotent stem cells, in therapeutic applications will require the development of robust, scalable culture technologies for undifferentiated cells. Advances made in large-scale cultures of other mammalian cells will facilitate expansion of undifferentiated human embryonic stem cells (hESCs), but challenges specific to hESCs will also have to be addressed, including development of defined, humanized culture media and substrates, monitoring spontaneous differentiation and heterogeneity in the cultures, and maintaining karyotypic integrity in the cells. This review will describe our current understanding of environmental factors that regulate hESC self-renewal and efforts to provide these cues in various scalable bioreactor culture systems.